The relationship between patient knowledge and behavior of NSAID self-medication at Pharmacy X in Banjarmasin - Guntur Kurniawan; Muhammad Reza Pahlevi; Helmina Wati; Wulan Ageng Sujatmiko (Jurnal Ilmiah Farmasi, 2023)
Background: Self-medication is a way of providing treatment for oneself without a doctor's prescription or the unwanted effects of a drug. Knowledge about diseases and drugs is needed to determine the right behavior for self-medication. One of the drugs used by the public is the non-steroidal anti-inflammatory drug (NSAID).Objective: The purpose of this research was to evaluate the correlation between patient knowledge of using NSAIDs and patient behavior at Pharmacy X, located in Banjarmasin. Method: This research used a quantitative method with a cross-sectional approach. This study included 40 patients who visited Pharmacy X in Banjarmasin for 1 month. The respondents were enrolled using the accidental sampling technique. The data was obtained with a questionnaire and analyzed with the Pearson Chi Square method. Results: The outcomes of this study indicated that the knowledge level of respondents on NSAIDs was classified as poor (40%). The behavior of subjects who use NSAIDs for self-medication was categorized as negative (62.5%). This study also showed an association between knowledge and habits of self-medication using NSAIDs at pharmacy X in Banjarmasin, with a significance value of 0.003 (p <0.05).Conclusion: There is a direct proportional relationship between knowledge and self-medication behavior when taking NSAIDs, with a significance value of 0.003 (p < 0.05). Intisari Latar belakang: Swamedikasi adalah cara melakukan pengobatan sendiri tanpa resep dokter maupun pengetahuan tentang reaksi obat yang tidak diinginkan. Pengetahuan tentang penyakit dan obat sangat dibutuhkan untuk menentukan perilaku yang benar dalam pemilihan obat secara mandiri. Salah satu jenis obat yang digunakan oleh masyarakat adalah obat golongan Non-Steroidal Anti-Inflammatory Drugs (NSAID).Tujuan: Penelitian bertujuan untuk mengetahui hubungan antara pengetahuan pasien tentang swamedikasi obat golongan NSAID dengan perilaku pasien di Apotek X Banjarmasin.Metode: Penelitian ini menggunakan metode kuantitatif dengan pendekatan cross-sectional. Studi ini melibatkan 40 responden yang berkunjung di Apotek X Banjarmasin selama 1 bulan. Pengambilan sampel menggunakan teknik accidental sampling. Pengumpulan data menggunakan kuesioner dan data dianalisis dengan uji Pearson Chi Square.Hasil: Hasil riset menunjukkan bahwa pengetahuan responden tentang NSAID termasuk dalam kategori â€œkurang baikâ€ sebanyak 40%. Perilaku pasien yang menggunakan swamedikasi obat NSAID termasuk dalam kategori â€œberperilaku negatifâ€ sebanyak 62,5%. Pengetahuan berhubungan dengan perilaku swamedikasi NSAID di Apotek X Banjarmasin dengan nilai signifikansi 0,003 (p<0,05). Kesimpulan: Pengetahuan pasien berbanding lurus dengan perilaku swamedikasi obat golongan NSAID.Kata kunci: tingkat pengetahuan, perilaku, swamedikasi, NSAID